In the garden of beasts [large type] : love, terror, and an American family in Hitler's Berlin - Larson, Erik, 1954- (Random House Large Print, 2011)
Documents the efforts of the first American ambassador to Hitler's Germany, William E. Dodd, to acclimate to a residence in an increasingly violent city where he is forced to associate with the Nazis while his daughter pursues a relationship with Gestapo chief Rudolf Diels.